HAK ASIMILASI DALAM PERSPEKTIF HUKUM ISLAM (ANALISIS PERMENKUMHAM NOMOR 10 TAHUN 2020) - Siska Damayanti; Marsaid Marsaid (Universitas Islam Negeri Raden Fatah Palembang, 2021)
The policy of releasing prisoners in an effort to suppress the spread of Covid 19, better known as the Corona virus is the government's authority. Where the Decree of the Minister of Law and Human Rights reads